2014
DOI: 10.1089/ten.tea.2013.0347
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cells of the Apical Papilla Regulate Trigeminal Neurite Outgrowth and Targeting through a BDNF-Dependent Mechanism

Abstract: Regenerative endodontic procedures have become a valuable alternative for the treatment of immature teeth with pulp necrosis. In addition to resolution of periradicular pathosis and promotion of continued root development, positive vitality testing has been observed in some regenerative clinical cases. Importantly, the positive response to electric stimulation of the regenerated tissue requires targeting of periradicular axons into the previously empty root canal space. However, the mechanism by which this pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 71 publications
1
47
0
Order By: Relevance
“…Promotes neuronal growth and axonal targeting and may bind to glycosaminoglycans, which is a possible mechanism for interaction and storage in the extracellular dentine matrix (De Almeida et al 2014). Glial cell line-derived growth factor (GDNF)…”
Section: Neurotrophic Factorsmentioning
confidence: 99%
“…Promotes neuronal growth and axonal targeting and may bind to glycosaminoglycans, which is a possible mechanism for interaction and storage in the extracellular dentine matrix (De Almeida et al 2014). Glial cell line-derived growth factor (GDNF)…”
Section: Neurotrophic Factorsmentioning
confidence: 99%
“…A recent study [145] demonstrated that SCAP release BDNF responsible for triggering directed axonal targeting both in vitro and in vivo , as shown by microfluidic and Matrigel implant experiments. Yu et al also detected several neurotrophic factors in SCAP secretome, including Midkine (MDK), Pleiotrophin (PTN), Mesencephalic Astrocyte-Derived Neurotrophic Factor (MANF), Neuroblast Differentiation-Associated Protein (AHNAK), and Neurophilin 2 (NRP2).…”
Section: Differentiation Potential and Paracrine Activity Of Dentamentioning
confidence: 99%
“…In addition, BDNF and NGF are well known to be involved in both the differentiation of new neurons and the protection/survival of established differentiated cells (Gu et al, 2009;Li et al, 2009;Salgado et al, 2010). Notably, BDNF regulates trigeminal neurite outgrowth (de Almeida et al, 2014). The survival of endothelial cells is promoted by MMP-3 and VEGF by their antiapoptotic actions (Gera et al, 1999;Chavakis and Dimmeler, 2002;Zheng et al, 2009), while GDNF also inhibits cell death in dental pulp (Gale et al, 2011).…”
Section: Discussionmentioning
confidence: 99%